Immersive Technology: A Bibliometric Analysis of Extended Reality Research Trends in STEM Education - Radhiani, Ahyani; Abouseada, Farouk (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to conduct a comprehensive review of the development of research on the use of XR technology in STEM education and its current status. Methodology: A bibliometric review method was used in this study. Data related to research on the use of XR technology in STEM education during the period 2011-2025 was collected through the Scopus database. A total of 138 articles were selected for analysis. The dataset search was conducted from September 30, 2025, to October 1, 2025. Data analysis was performed using Biblioshiny software from Bibliometric RStudio and VOSviewer. Main Findings: The results show that there is long-term scientific interest in research on the use of XR technology in STEM education, with an average annual growth rate of 26.2 and an average number of citations per document of 32.55. In addition, keywords such as metaverse, gamification, and virtual environment have significant potential in terms of future research, assuming that these keywords will be developed and integrated into STEM curricula and pedagogy. Novelty/Originality of this study: This study offers an innovative contribution by integrating bibliometric analysis with an evaluation of XR implementation trends in STEM education, going beyond descriptive reviews. It identifies key research gaps, underexplored areas, and the potential impact of XR on learning effectiveness. The findings provide a practical foundation for educators, researchers, and policymakers to design measurable, effective, and sustainable XR-based learning strategies, while strengthening both methodological and practical contributions to immersive STEM education research.